Fluoride release capacities of four different orthodontic adhesives - (:unkn) unknown (My University, 1999)
The aim of this study was to evaluate the fluoride release capacities of four orthodontic light cured adhesives. Groups 1 and 2 were the composites, Transbond and Sequence; Groups 3 and 4 were the glass ionomer cements, Fuji Ortho LC and 3M. Ten disc shaped specimens were prepared from each adhesive, and placed into a 1 ml of distilled water at 37 degrees C. The measurements were taken every day for a week, then once a week till the end of the first month, and once in two weeks till the end of the third month. The total and daily released fluoride amount during the testing period was statistically analyzed. The difference between the composite and glass ionomer cements was obvious. All the groups were statistically different from each other (p < 0.001). When the daily fluoride release graphics were detected, a sudden decrease was seen for all the adhesives. The fluoride values of the composites decreased to almost zero after the second day. The glass ionomer cements showed a decrease, too, but, they remained at a high level.
Keywords: Polyurethanes; Materials Testing; Analysis of Variance; Acrylic Resins; Statistics, Nonparametric; Orthodontic Brackets; Dentin-Bonding Agents; Dental Bonding; Aluminum Silicates; Glass Ionomer Cements; Resin Cements; Bisphenol A-Glycidyl Methacrylate; Fluorides; Methacrylates